Probability Analysis Of Employee Performance From Relevance To Position, Team Work, And Technical Ability - Siregar, Muliahadi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
The work model in each organization is different, depending on its characteristics. The work model in self-government agencies, such as the ministry of defence, has the character of a line of command work. Even though the characteristics of the work are civil, the character of the leadership's orders is attached to carrying out the duties. Technically, these work characteristics have advantages in maintaining performance, where employees will be more committed to the tasks they have carried out. This study aims to analyze the possibility of increasing or decreasing performance based on several factors, including the suitability of the job/position/position relevance, work team, and work skills. The method used is quantitative with path analysis techniques. The samples for this study were 70 civil servants of the Indonesian Ministry of Defense using a simple random sampling technique. The results of the study show that the employee's work results will be better if he is placed in a work position that is in accordance with his knowledge and expertise, especially if it is supported by good work skills and a solid work team, then the possibility of performance increasing is very high. Mathematically, this study recommends a path model in improving employee performance, where job relevance/job relevance can be a trigger for optimizing skills and a solid work team